Low fidelity model making activity by students: A novel way of learning concepts of neuroanatomy. (June 2018) - Dixit, Shilpi Gupta; Potaliya, Pushpa; Nayeemudin, S.M.; Ghatak, Surajit
Highlights: Neuroanatomy tracts/pathways is a complex topic that has always faced innate and contextual challenges. Assessment of the effectiveness of a relatively simple model making activity for better understanding of neuroanatomy by first year medical undergraduate students. Student feedback of neuroanatomy activity was taken and their opinion to supplement it as an integral part of curriculum was also explored. 81 and 82.4% of students stated that the activity was clearly explained and should be offered more frequently in curriculum. The activity also developed a positive attitude and good coordination amongst peers with increase in communication skills (89.1%, 91.8%, 89% respectively). A low-cost learning intervention formulated to deliver a complex 3-D model of tracts passing through various parts of nervous system by simple materials would show better access and understanding of the tracts with improvement of 3D visualization skills innovative method. Abstract: Teaching and learning anatomy has always been an integral part of medical education. Teaching neuroanatomy has always faced innate and contextual challenges therefore various innovative teaching-learning methods have been devised on the idea of engaging learners in meaningful learning activities through apt guidance, communication among peers and cluster activities. The present study aims at such an innovative method. The study was conducted in practical sessions of first year MBBS at the Institute during second semester. Neuroanatomy topic selected for present study was 'Neural Pathways/tracts'. Participants were divided into 8 groups and each was allotted a specific activity related to a particular cross-sectional level and allowed to build with the material provided by the department. Student feedback was taken through a structured questionnaire. 81 and 82.4% of students stated that the activity was clearly explained and should be offered more frequently in curriculum. The activity also developed a positive attitude and good coordination amongst peers with increase in communication skills (89.1%, 91.8%, 89% respectively). 87.8% of students agreed that small group learning is better than didactic lectures in neuroanatomy. In current medical scenario with reduced anatomy teaching hours and a continuous pressure on undergraduates, a low-cost learning intervention formulated to deliver a complex 3-D model of tracts passing through various parts of nervous system by simple materials would show better access and understanding of the tracts with improvement of 3D visualization skills.